Analysis of the cell-free amniotic fluid transcriptome expressed during the euploid mid-trimester of pregnancy. (August 2016) - Jung, Yong Wook; Shim, Sung Shin; Park, Ji Eun; Sung, Se Ra; Shim, Sung Han; Park, Hea Ree; Cha, Dong Hyun
Abstract: Objective: The amniotic fluid (AF) contains cell-free RNAs (cfRNAs), which are considered to reflect the fetal status in utero . However, there are limited numbers of data to examine the AF cell-free transcriptome because amniocentesis is an invasive procedure. In this study, the AF transcriptome expressed during the euploid mid-trimester of pregnancy was characterized. Study design: Fourteen AF samples were collected. RNA was extracted from AF supernatant, hybridized to Affymetrix GeneChip Human arrays, and the transcriptome was analyzed by using the DAVID toolkit. Result: We detected 1069 genes in the 14 AF samples. The GNF atlas mapping showed that genes present in the AF were annotated with endocrine organs and blood components, including the pancreas, adrenal gland, thyroid, ovary and monocytes. The proteins encoded by the transcriptome were localized to several organs, which are directly in contact with the AF, including the placenta, lung, skin, epithelium, and kidney. During the early fetal period, there is a bi-directional diffusion between the fetus and AF. Therefore, the AF composition is similar to that of the fetal plasma. In addition, fetal urine, swallowing, pulmonary secretion, and diffusion across the placenta contribute to produce amniotic fluid by directly excreting fluid. The KEGG pathway analysis with placenta specific genes revealed that focal adhesion and extracellular matrix receptor interaction pathways were enriched. These pathways are important for the placental development. Conclusion: cfRNA in the amniotic fluid originates from placenta and fetal organs directly contacting the amniotic fluid as well as from diffusion of the fetal plasma across the placenta. AF transcriptome may reflect not only fetal development, but also placental development.